(untitled) (Islas, 2023)
Introduction: Among the terminology studies based on specialized contents, the poly-lexical character stands out. The nominal composition is one of the procedures by means of which these are elaborated. This paper evaluates the presence and values of these kinds of terms concerning the occupational area of the Cuban Rum production. Methods: Grammar and semantic analysis specialized methods are applied in the study of the nominal compounds extracted from research studies and scientific papers developed within the specialty in central Cuba. Results: It offers a description of the nominal compounds according to their quantity and nature (formal and significant) of its parts, their contribution to the notion of compound and implicit relations, the semantic category the nominal compounds belong to and the signified relations established among them. Conclusions: Assessment on the quantity and nature (formal and significant) of its parts, their contribution to the notion of compound and implicit relations, the semantic category the nominal compounds belong to and the signified relations established among them.